Peranan Etnis Tionghoa Muslim Pada Masa Kolonial Belanda, Abad ke-19 di Palembang: The Role of Chinese Muslim Ethnicity in the Dutch Colonial Period, 19th Century in Palembang - Anggela, Wela Celsi (Journal of Islamic History, 2021)
This Study describes the historical series of the role of the Chinese Muslim etnich group in the 19th century Dutch colonial period in Palembang, in this article will reveal several Chinese Muslim ethnich figures and clerics who played a role in the 19th century Dutch colonial period in Palembang, including; Kiyai Mas Husin (Yu-Chien), Baba Yu Chien has a son named Muhammad Najib I who holds the title of Kiyai Demang Jayosepuh Wiraguno who served as a minister during the reign of Sultan Ahmad Najamuddin, Baba Balqiyah and Baba Mas’ud, they played a role in resisting the Dutch colonial and drowning Dutch cruise ship at the mouth of the Ogan river in Palembang. After they died, his role was replaced by Baba Muhammad Najib II or Kiyai Demang Jayalaksana who was an important figure in the construction of the Great Mosque of Palembang in the reign of Sultan Muhammad Badaruddin II (1724 M/1137 H). The majority are Muslims from the Dutch colonial nation.